Literatur Review Implementasi The Flipped Classroom: Apakah Efektif Terhadap Learning Outcomes Peserta Didik pada Abad 21? - Kesumah, Mayang Dela; Siburian, Jodion (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract: The goal of this study was to analyze and evaluate the effectiveness of the implementation of the flipped classroom on learning outcomes of 21st century students through literature review. This study uses a literature method from 22 journals that have the subject of the flipped classroom. These journals were obtained from the Google Scholar database for the 2020-2024 range. The results of the literature of almost all journals show that there is a positive and quite significant difference in learning outcomes in the implementation of the flipped classroom compared to traditional learning models. 90.9% of journals show that the implementation of the flipped classroom can improve students’ higher order thinking skills (HOTS), while 9.1% of other journals show no difference with traditional learning models.Abstrak: Tujuan dari penelitian ini untuk menganalisis dan menilai efektivitas implementasi the flipped classroom terhadap learning outcomes peserta didik abad ke-21 melalui tinjauan literatur. Penelitian ini menggunakan metode literatur dari 22 jurnal yang memiliki pokok bahasan the flipped classroom. Jurnal ini diperoleh dari Google Scholar database dari tahun 2020-2024. Hasil dari literatur menunjukkan bahwa terdapat perbedaan learning outcomes yang positif dan cukup signifikan dalam implementasi the flipped classroom dibandingkan dengan model pembelajaran tradisional. 90.9% jurnal menunjukkan implementasi the flipped classroom mampu meningkatkan Higher Order Thinking Skills (HOTS) peserta didik, sedangkan 9.1% jurnal lainnya tidak terdapat perbedaan dengan model pembelajaran tradisional.